An ultraviolet B condition that affects growth and defense in Arabidopsis. (March 2018) - Vandenbussche, Filip; Yu, Na; Li, Weidong; Vanhaelewyn, Lucas; Hamshou, Mohamad; Van Der Straeten, Dominique; Smagghe, Guy
Highlights: Identification of an UV-B condition for plant growth reduction without obvious detrimental stress. UV-B causes decreased stomatal density and enhanced photoprotective pigmentation. The UV-B rosette leaf transcriptome suggests enhanced defense responses. Insect performance on Arabidopsis in UV-B conditions is species dependent. Abstract: Ultraviolet B light (UV-B, 280–315 nm) is the shortest wavelength of the solar spectrum reaching the surface of the Earth. It has profound effects on plants, ranging from growth regulation to severe metabolic changes. Low level UV-B mainly causes photomorphogenic effects while higher levels can induce stress, yet these effects tend to overlap. Here we identified a condition that allows growth reduction without obvious detrimental stress in wild type Arabidopsis rosette plants. This condition was used to study the effects of a daily UV-B dose on plant characteristics of UV-B adapted plants in detail. Exploration of the transcriptome of developing leaves indicated downregulation of genes involved in stomata formation by UV-B, while at the same time genes involved in photoprotective pigment biosynthesis were upregulated. These findings correspond with a decreased stomatal density and increased UV-B absorbing pigments. Gene ontology analysis revealed upregulation of defense related genes and meta -analysis showed substantial overlap of the UV-B regulated transcriptome with transcriptomes of salicylate and jasmonate treated as well as herbivore exposed plants. Feeding experiments showed that caterpillars of Spodoptera littoralis are directly affected by UV-B, while performance of the aphid Myzus persicae is diminished by a plant mediated process.